Biomechanical responses to water fitness programmes: a narrative review - Santos, Catarina C. (2020)
In the past years, there was an increasing interest in the biomechanical responses in water fitness sessions. The present review consolidates the current “state-of-art” on the biomechanical responses in water fitness programmes. The literature was searched and screened studies on: (i) healthy subjects; and (ii) water fitness sessions and programmes reporting physical condition outcomes. A total of 36 studies met the inclusion criteria and categorized into four categories: (i) kinematics (n = 5); (ii) ground reaction force (n = 10); (iii) neuromuscular (n = 8); and (iv) strength (n = 14). There was a larger amount of evidence on strength, whereas some gaps in the body of knowledge still persist in the remaining categories. The existent studies cover a large range of age brackets (from young adults to the elderly). Women were recruited more often than men to be part of the studies. The effect of music cadence, body segments, exercise type (e.g., alternated or simultaneous), water depth, resistance equipment, and training protocols were the main topics under research.